Sports, Power, and Communication: the Image Challenges of Formula 1 in Authoritarian Countries - Dzhambazova, Tsvetelina (Media and Language, 2025)
Formula 1, as a globally recognized sport with millions of viewers, attracts authoritarian states that use hosting races to improve their image through sportswashing. Through case study analysis, this article examines how Bahrain, Saudi Arabia, Qatar, and Azerbaijan utilize F1 to divert attention from human rights violations and other issues. The study considers the lack of response from F1 and the FIA as a significant problem that undermines the sport’s legitimacy. In conclusion, a communication strategy is proposed to address criticism of the organizations’ passivity.